2005
DOI: 10.1523/jneurosci.1735-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Complex Regulation of Spiral Ganglion Neuron Firing Patterns by Neurotrophin-3

Abstract: Auditory information is conveyed into the CNS via the spiral ganglion neurons, cells that possess distinctive electrophysiological properties that vary according to their cochlear innervation. Neurons from the base of the cochlea fire action potentials with shorter latencies and durations with more rapid accommodation than apical neurons (Adamson et al., 2002b). Interestingly, these features are altered by exposure to brain-derived neurotrophic factor and neurotrophin-3 (NT-3), suggesting that the electrophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 43 publications
4
42
1
Order By: Relevance
“…Another aspect of this reciprocal regulation is the apparent homogeneity in the neuronal population exposed to BDNF compared with the heterogeneity observed with NT-3. These differences have also been observed with previous electrophysiological analysis (Adamson et al, 2002b;Zhou et al, 2005); the functional significance, however, has yet to be explored directly.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Another aspect of this reciprocal regulation is the apparent homogeneity in the neuronal population exposed to BDNF compared with the heterogeneity observed with NT-3. These differences have also been observed with previous electrophysiological analysis (Adamson et al, 2002b;Zhou et al, 2005); the functional significance, however, has yet to be explored directly.…”
Section: Discussionsupporting
confidence: 52%
“…Presynaptic and postsynaptic proteins are differentially distributed within the spiral ganglion Previous studies have shown that although 95% of the neurons within the spiral ganglion are of one class, they display clear differences in their ion channel composition and resulting firing patterns (Mo and Davis, 1997;Adamson et al, 2002b;Reid et al, 2004;Zhou et al, 2005). Neurons that innervate high frequency sensory receptors at the basal end of the cochlea possess voltagegated ion channel types that mediate abbreviated and rapidly accommodating responses to prolonged step depolarizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine potential mediators of these changes, we examined the effects of NT-3, the expression of which is reduced during this same time period. Based upon previous studies, we expected that P5 basal spiral ganglion neurons would be converted from RA to SA, that voltage thresholds would be reduced, and that latencies would be prolonged after exogenous application of NT-3 (Adamson et al, 2002b;Zhou et al, 2005). Here, we expanded on those observations by assessing the effects of NT-3 (10 ng/ml) on basal and apical neurons by examining both earlier (P3, slower but highly excitable), intermediate (P8), and later (P10-P14, faster but reduced excitability) time points.…”
Section: Resultsmentioning
confidence: 99%
“…The stock solution was diluted with sterile distilled water and added at time of plating to a final concentration of 10 ng/ml (1:1000 dilution). This concentration was chosen because it yielded the maximal change in accommodation (Zhou et al, 2005). Vehicle control was 10 l of sterile distilled water added at time of plating.…”
Section: Introductionmentioning
confidence: 99%